Recent advances on food‐based applications of monoglyceride oleogels - Palla, Camila A.; Dominguez, Martina; Carrín, María Elena (Journal of the American Oil Chemists' Society, 2022)
Monoglyceride (MG) oleogels are soft matter structures designed to mimic the functionality of fats while maintaining a lipid profile comparable to that of edible oils. These novel fat materials have been mainly investigated as ingredients to reduce saturated fats and eliminate trans fats in the production of several foods, such as spreadables, bakeries, confectioneries, and meat products among others. Due to the versatility that oleogels offer, other relevant technological functionalities as well as the development of health‐promoting systems have been the subject of extensive research. MG oleogels have been explored as oil migration inhibitors, emulsion stabilizers, lipid oxidation stability enhancers, and even as 3D printing materials. Among the most recent applications are the use of MG oleogels as carriers of bioactive compounds as well as the development of systems able to modulate lipid digestion. This review exclusively focuses on the advances over the last decade in technological and nutritional applications of MG oleogels and MG oleogel‐based systems, outlining the most significant findings and conclusions from the literature, as well as challenges and trends for future studies.